ข้อมูลใหม่กับกลไกการออกฤทธิ์และสหสัมพันธ์ทางคลินิกของแกรนูไลซิน - วรรณิสสร เนตรนภิส; วรรณิสสร ประทีป (Health Science, Science and Technology Reviews, 2015)
แกรนูไลซินเป็นโปรตีนพบในเซลล์เพชฌฆาตตามธรรมชาติหรือเซลล์ทำลายสิ่งแปลกปลอม มีคุณสมบัติด้านจุลชีพประกอบด้วยต้านจุลชีพเกิดโรคในเซลล์และต้านมะเร็ง กลไกด้านจุลชีพประกอบด้วย 1) การแทงทะลุสิ่งหุ้มจุลชีพ 2) การฆ่าด้วยความเครียดออกซิเดขั่นหลังจากแกรนูไลศินส่งแกรนไซม์บีเข้าในเซลล์จุลชีพลดฤทธิ์เองไซม์ความเครียดด้านออกซิเดชั่น และ 3) ฆ่าโดยแกรนูไลซินและเพอฟอรินในเซลล์เพชฌฆาตตามธรรมชาติ ขณะที่การฆ่าจุลชีพในเซลล์ต้องการเพอฟอริน เพื่อส่งแกรนูไลซินและแกรนไซบีเข้าไปเซลล์เจ้าบ้าน ภายในเซลล์แกรนูไลซินปล่อยแกรนไซม์บีเข้าชีพตายด้วยความเครียดออกซิเดชัน กลไกต้านมะเร็งประกอบด้วย 1) แกรนูไลซินทะลุเข้าเซลล์มะเร็งแล้วโจมตีไมโทคอนเดรีย ปลุกฤทธิ์แคสเปส 9 แคสเปส 3 นำไปสู่กระบวนการตายของเซลล์ และ 2) เซลล์เพชฌฆาตตามธรรมชาติใช้เพอฟอรินเพื่อส่งแกรนูไลซินเข้าไปในเซลล์มะเร็ง ทำลายร่างแหเอนโดพลาซึม ปลุกฤทธิ์แคสเปส 7 นำไปสู่กระบวนการตายของเซลล์ แกรนูไลซินเกี่ยวข้องกับโรคติดเชื้อ มะเร็ง และโรคภูมิต้านทานต่อตนเอง ความรู้ใหม่ของแกรนูไลซินและกลไกการออกฤทธิ์อาจมีประโยชน์สำหรับการป้องกันและเยียวยาโรคในอนาคต Granulysin, an update on mechanism of action and clinical correlation Netnaphis Warnnissorn1*, Prateep Warnnissorn2 1 Department of Biochemistry, Faculty of Medical Science, Naresuan University, Phitsanulok Province 65000 2 Department of Internal Medicine, Faculty of Medicine, Naresuan University, Phitsanulok Province 65000 Granulysin is a protein found in natural killer (NK) cells or cytotoxic T lymphocytes. Its properties are antimicrobial, including against intracellular pathogen, and anticancer. The mechanisms of antimicrobial include 1) perforating the envelop of microbes, 2) oxidative stress killing after granulysin sends granzyme B into bacterial cells, inactivating antioxidative stress enzymes and increase reactive oxygen species, and 3) killing by granulysin and perforin from NK cells. While intracellular bacterial killing requires perforin to send granulysin and granzyme B into the host cell. In the cell granulysin delivers granzyme B into the bacteria. Granzyme B inactivates antioxidative stress mechanisms, raises reactive oxygen species and bacteria die of oxidative stress. Anticancer mechanisms are 1) granulysin cleavage into tumor cells to attack mitochondria, activates caspase 9 and caspase 3 that lead to apoptosis, and 2) NK cells use perforin to send granulysin into tumor cells damaging endoplasmic reticulum and activate caspase 7 that also lead to apoptosis. Granulysin is associated with infectious diseases, cancers and autoimmune diseases. The update knowledge of granulysin and its mechanism of action might be useful for preventing and curing diseases in the future.